Continuous auditing: Developing automated audit systems for fraud and error detections - Gregorius Rudy Antonio (Universitas Hayam Wuruk Perbanas, 2014)
Indonesian Institute of Certified Public Accountants, American Institute of Certified Public Accountants and the Canadian Institute of Chartered Accountants(SAS 99 sec 110, par 2) establishes auditors’ responsibility to plan and perform the audit to obtain reasonable assurance about whether the financial statements are free of material mis- statement, whether caused by error or fraud to plan and perform audits to provide a reasonable assurance that the audited financial statements are free of material fraud. This study proposed the development of Automated Audit System model to assist auditors in bridging them to the challenges in detecting fraud. This approach firstly provides a framework to have better understanding about the business process and data structures of information systems which is required in establishing an effective audit program. These ingredients are mapped in the audit process, including audit objectives, internal control and audit rules by using the Use-Case Diagram, Data Flow Diagram and Entity Relationship Diagram. Second, this study employs Ben- ford’s Law and Automatic Transaction Verification for the detection of anomalies and irregularities to design the framework. It also presents a systematic case study of ac- tual continuous auditing in department stores that using ERP systems. It is expected to detect frauds and errors. It proves that Continuous Audit and Benford Law can establish strong framework in Automated Audit Systems for Fraud Detections and finally provide a big contribution to internal control and company policies.